The association between bullying victimization in childhood and fibromyalgia. Data from the nationwide Finnish health and social support (HeSSup) study based on a sample of 64,797 individuals - Varinen Aleksi; Kosunen Elise; Mattila Kari; Suominen Sakari; Sillanmäki Lauri; Sumanen Markku (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Background: Fibromyalgia is a functional pain syndrome presenting with various psychological symptoms. Several studies have shown that adverse life events are associated with fibromyalgia. The aim of the current study is to explore the association between self-reported bullying victimization in childhood and self-reported fibromyalgia in adulthood.
Methods: The basic study setting is cross-sectional- with focused use of retrospective data- derived from a large on-going postal follow up survey (sample N = 64,797) initiated in Finland in 1998. Only respondents having answered the questions on fibromyalgia in both follow ups in 2003 and 2012 were included (N = 11,924). Severity of bullying was divided into three groups starting from no bullying followed by minor and severe Covariates having shown statistically significant associations with fibromyalgia in cross tabulation using Pearson's chi-squared test were included in the final multiple logistic regression analyses.
Results: In our study, 50.6% of the respondents reported victimization of minor and 19.6% of severe bullying in childhood. Participants reporting fibromyalgia in adulthood reported more bullying, and in females alone this association was statistically significant (p =.027). In multiple logistic regression analysis statistically significant associations between bullying victimization in childhood (reference: no bullying) and fibromyalgia were found: adjusted odds ratio (OR) for minor bullying was 1,35 (95% CI 1.09-1.67) and for severe bullying 1.58 (95% CI 1.21-2.06). However, in log-linear and logistic regression interaction models the association between bullying and fibromyalgia was not statistically significant when depression was included in the models.
Conclusions: Our results suggest that peer bullying victimization might be associated with fibromyalgia. However, in logistic log linear and logistic interaction models there was no statistically significant association when depression was included. As a result, there is need for further, preferably prospective cohort studies. The findings also emphasize the importance of actions to prevent childhood bullying.